Islamic fasting reduce body weight and improves blood lipid profile in normal and obese subjects - Khattak, Muhammad Muzaffar Ali Khan (The International Chair on Cardiometabolic Risk, 2010)
Fasting is performed in different communities with different believes and for the management of body weight but in Islam the Muslim observes fasting in the Holy Month of Ramadan as an obligation. Therefore, this study was designed to know the effect of fasting on the obesity factors for example body weight, serum adiponectin and serum lipids. Twenty five volunteers (male & female) from the International Islamic University Malaysia (IIUM) were recruited in Ramadan. Age, sex, weight, height and menstrual cycle status (in case of females) were recorded on day 1 of the Ramadan and body weight was also recorded on day 21. Blood samples were collected on the Day 1 of the Ramadan followed by another three collection of blood samples on day 7, 14 & 21 respectively. The blood serum was separated and stored at 20C̊. From weight & height, Body Mass Index (BMI) was determined. The blood was analyzed for glucose, adiponectin and lipid profiles by Bayer Health Care Kits. After 21 days of Ramadan, fasting body weight was significantly (P <0.001) reduced in the obese individuals. There was a decreasing trend in blood glucose concentration from day 1-21 and the decrease was 10.00 percent. The blood triglyceride concentration significantly reduced and the reduction was 17.48 percent from day 1-21. The blood total-Cholesterol concentration also reduced from day 1-21 and the reduction was 15.93 percent. The blood LDL-Cholesterol concentration also significantly reduced from day 1-21 and the reduction was 21.67 percent. The blood HDL-Cholesterol concentration decreased in the first week and second week but improving in trend was observed on day 21 of the Ramadan. This study indicates that Islamic fasting could be a useful tool for the management of body weight and blood lipids without having major shift in the body composition.